2022
DOI: 10.3390/ijerph19116606
|View full text |Cite
|
Sign up to set email alerts
|

Cardioversion of Post-Ablation Atrial Tachyarrhythmia with Ibutilide and Amiodarone: A Registry-Based Cohort Study

Abstract: Patients with recurrence of atrial tachyarrhythmia after catheter ablation for atrial fibrillation or atrial flutter constitute a rapidly growing cohort, but study-driven treatment recommendations are lacking. The present study aimed to compare the cardioversion success of ibutilide and amiodarone in patients with post-ablation atrial tachyarrhythmia. We included all episodes of post-ablation atrial tachyarrhythmia in patients treated with either intravenous ibutilide or amiodarone at an academic emergency dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
1
0
0
Order By: Relevance
“…The main findings of our trial are in line with a study by Cacioppo et al, who found that cardioversion with intravenous amiodarone led to the return of sinus rhythm in 31.6% of patients (n = 6/19) [20]. In this study, amiodarone was far less efficacious than IV ibutilide (90%, n = 18/20; OR 19.5); however, it was characterized by a relatively low study count [20]. In our study, no adverse actions of amiodarone were reported, while in the abovementioned study, bradycardia was documented in two patients (3%).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The main findings of our trial are in line with a study by Cacioppo et al, who found that cardioversion with intravenous amiodarone led to the return of sinus rhythm in 31.6% of patients (n = 6/19) [20]. In this study, amiodarone was far less efficacious than IV ibutilide (90%, n = 18/20; OR 19.5); however, it was characterized by a relatively low study count [20]. In our study, no adverse actions of amiodarone were reported, while in the abovementioned study, bradycardia was documented in two patients (3%).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, 24.3% of patients with AFl proceeded directly to ablation, while in 16.2% of patients the procedure was postponed and scheduled for subsequent hospitalization following initial rate and rhythm control management. These data deliver evidence of a suboptimal approach to AFl management, presumably deriving The main findings of our trial are in line with a study by Cacioppo et al, who found that cardioversion with intravenous amiodarone led to the return of sinus rhythm in 31.6% of patients (n = 6/19) [20]. In this study, amiodarone was far less efficacious than IV ibutilide (90%, n = 18/20; OR 19.5); however, it was characterized by a relatively low study count [20].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation